Effect of laser shock peening on high cycle fatigue characteristics of 316LN stainless steel. (September 2019) - Yella, Pardhu; Rajulapati, K.V.; Prasad Reddy, G.V.; Sandhya, R.; Prem Kiran, P.; Buddu, Ramesh K.; Bhanu Sankara Rao, K.
Abstract: The influence of 'laser shock peening' (LSP) on fatigue behavior of 316LN stainless steel has been studied at 298 K by conducting fully reversed stress controlled fatigue tests in the range 200–300 MPa. A triangular wave form with a constant frequency of 5 Hz was employed for all the tests conducted below 10 7 cycles on the virgin and laser shock peened samples. The run out tests at 10 7 cycles were performed at a frequency of 60 Hz. The studies have clearly revealed that the fatigue life is dependent on surface condition of the material and stress amplitude employed. A comparison is made of cyclic stress-strain hysteresis loops and fatigue lives between virgin and peened material. The peened material showed better fatigue strength and life at low stress amplitudes pertaining to high cycle fatigue regime, and exhibited lower density of surface microcracks. The improved fatigue resistance of peened material is attributed to the presence of residual compressive stresses to a depth of ~100 μm from the surface. The beneficial effect of compressive stresses is perceived both in the reduction in number density of Stage-I microcracks and retarded stage-II crack growth in the initial stages (that revealed striations with lesser spacing compared to un-peened samples). Highlights: Laser shock peening (LSP) induced surface compressive stresses upto ~100 μm depth. LSP resulted in low density of surface microcracks in fatigue tested samples. Fatigue life of LSP samples improved by about 12.5% compared to unpeened ones. Finer striation spacings (in stage-II) observed at near surface regions of LSP samples. Striation spacing in stage-II in unpeened samples is large compared to LSP ones.